ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI HASIL TANGKAPAN NELAYAN DI KECAMATAN BILATO KABUPATEN GORONTALO - Julindri N. Puluhulawa; Asda Rauf; Amir Halid (Universitas Negeri Gorontalo, 2016)
This research aims at (1) Finding out the tendency for number of fish landed in Bilato Sub-district; (2) Finding out the factors that influence the number of fish caught by the fishermen in Bilato Sub-district. (3) Finding out the fishermen income in Bilato Sub-district. This research was carried out from June to july 2015. The analysis method used in this research is descriptive analysis and multiple linier regression analysis, and income analysis. This descriptive analysis is used to find out the tendency of number of fish caught by the fishermen in Bilato Sub-district, the multiple linier regression analysis is used to find out the factors that influence the number of fish caught by the fishermen, on the other hand, the income analysis is used to find out the amount of fishermen income in Bilato Sub-district. This research reveals that (1)Tthe tendency of number of fish caught by the respondents fishermen in Bilato Sub-district in July through September are fluctuated in which, the largest amount of fish caught was in July where 4,797 kg of fish was caught and the least amount of fish caught was in October 2015, with only 1,674 kilos of fish caught. (2) Production factors, capital, boat, and workers simultaneously significantly influenced the number of fish landed. Mean, partially, only production factor of cost that significantly influenced, mean, production factors such as boat and workers insignificantly influenced the number of fish landed. (3) The average income of respondents I Bilato Sub-district was IDR 24.847.657 in a year. Keywords: Fishermen,Tendency, Income